French economists and the symbolic power of (post-)national capital: Taking sides in discourses of crises, 2008–2021 - Schmidt-Wellenburg, Christian (Serendipities. Journal for the Sociology and History of the Social Sciences, 2024)
The paper argues that economists’ position-taking in discourses of crises should be understood in the light of economists’ positions in the academic field of economics. This hypothesis is investigated by performing a multiple correspondence analysis (MCA) on a prosopographical data set of 144 French economists who positioned themselves between 2008 and 2021 in controversies over the euro crisis, the French political economic model, and French economics. In these disciplinary controversies, different forms of (post-)national academic capital are used by economists to either initiate change or defend the status quo. These strategies are then interpreted as part of more general power struggles over the basic national or post-national constitution and legitimate governance of economy and society.